Bariatric surgery in the treatment of patients with obesity and type 1 diabetes: A retrospective study of clinical data. Issue 7 (29th March 2021) - Mohammed, Nagi; Buckley, Adam; Elsheikh, Mohgah; Allum, Matthew; Suliman, Sara; Al Hadad, Mohammed; le Roux, Carel W; Lessan, Nader; Suliman, Mohamed
Abstract: Aim: To evaluate the effectiveness and safety of bariatric surgery in patients with coexisting type 1 diabetes and obesity who choose to undergo bariatric surgery for weight management. Materials and Methods: We conducted a retrospective, longitudinal review of the clinical data of patients with type 1 diabetes, followed up at our centre after bariatric surgery had been performed elsewhere. Results: Sixty‐one patients were included, of whom 51% were women, and 57 (93%) were Emirati Arab, three (5%) were other Arab, and one (2%) was White in ethnic origin. The mean age at surgery was 31 years. A total of 42 patients (69%) underwent sleeve gastrectomy, 17 (28%) gastric bypass, and two (3%) gastric banding. In 48 patients with complete follow‐up data, improvements were observed at 12 months in the median (interquartile range [IQR]) values for body mass index (BMI; 38.5 [34.9‐40.9] to 26.1 [24.2‐29.6] kg/m 2, P <0.001), glycated haemoglobin concentration (8.6 [7.8‐9.2]% to 7.8 [7.2‐8.5]%; P <0.001), daily insulin dose (1.0 [0.7‐1.2] to 0.8 [0.6‐0.9] units/kg/d; P <0.001), systolic blood pressure (127 [116‐136] to 116 [110‐120] mmHg; P <0.001), total cholesterol: high‐density lipoprotein cholesterol ratio (3.4 [2.9‐4.3] to 3.0 [2.6‐3.5]; P <0.001), and albuminuria. In 32 patients followed up at 3 years, the median (IQR) reduction in BMI was 10.4 (5.9‐11.7) kg/m 2, 50% reduced or stopped antihypertensive medication and 58% reduced or stopped lipid‐modifying medication. Three patients each reported a single episode of diabetic ketoacidosis; in one case this was due to cessation of insulin treatment. Conclusions: In our cohort of patients with obesity and type 1 diabetes, bariatric surgery led to significant improvements in weight and cardiometabolic variables, with modest improvements in glycaemia. Few adverse events were reported.